Representação política discursiva no facebook: análise da atuação de mulheres vereadoras - CAL LAGE, Danila Gentil Rodriguez (Associação Nacional dos Programas de Pós-Graduação em Comunicação, 2022)
We analyze how the discursive political representation of councilors is configured in a communicational environment in which they enjoy relative autonomy for production and publication, Facebook. Specifically, we will investigate the videos posted on the profiles and personal fan pages of city councilors (2017/2020) in the two main capitals of the North of the country: Belem and Manaus. As a theoretical foundation, we resort to the discussion on political representation, in particular, the discursive one. From a methodological point of view, the corpus is composed of 210 videos that were systematized through content analysis and analyzed from three categories linked to discursive political representation: how do they speak? how often? what are they talking about? The results point out tensions related to the demands of women's representation and the themes defended by the councilors, as well as shedding light on the aspects of format and language from which they seek to interact in that communicational environment.